The Carbon Dioxide Flushing Technique: A Novel Approach Using Oxygen Measurements to Evaluate the Elimination of Room Air from Thoracic Stent-Grafts - Arulrajah, Kugarajah; Kölbel, Tilo; Panuccio, Giuseppe; Gandet, Thomas; Rohlffs, Fiona (International Journal of Innovative Research in Medical Science, 2023)
Background: The study evaluates a novel technique using oxygen measurements to indirectly evaluate the behavior of carbon dioxide (CO2) in the residual gas released by thoracic stent-grafts and to better understand the mechanism of the CO2 flushing technique. Methods: Ten Zenith TX2 ProForm thoracic stent-grafts (ZDEG-PT-34-199-PF, Cook Medical, Bjæverskov, Denmark) were equally divided into 2 groups (Group A and B). Group A was flushed with 60 ml of 0.9% saline. Group B was flushed with 100% carbon dioxide gas followed by 60 ml of 0.9% saline. The stent-grafts were deployed into a plastic tube that was placed and fixated to the bottom of a translucent container filled with water to collect the residual air released by the stent-grafts. Oxygen (O2) concentration and gas volume were measured in the released gas. Results: The oxygen concentration was significant (p<0.001) lower after additional carbon dioxide flush compared to standard flush (18.5% vs 19.6%). Furthermore, the absolute oxygen volume was significantly lower after additional carbon dioxide flush than without (0.18 ml vs 0.32 ml, p=0.041). The total amount of released gas appeared lower with carbon dioxide flush than without (0.98 ml vs 1.65 ml, P=0.058). Conclusions: CO2 absorption into saline and replacement of room air by CO2 inside the stent-graft may lead to a reduction of released gas during stent-graft deployment in an experimental setting.